Togo 2016 - Dirk Kohnert (Africa Yearbook Volume 13: Politics, Economy and Society South of the Sahara in 2016, 2017)
President Faure Gnassingbé acted throughout the year from a position of strength, given the divided and weakened opposition. Overdue political and institutional reforms and local elections were postponed indefinitely. The human rights situation improved slightly, but the regime continued to be describable as `authoritarian'. In view of the growing jihadi risk in the sub-region, the international donor community rewarded Togo's apparent political stability as an anchor of security in West Africa with a substantial increase in development aid. With promising growth prospects, low inflation and an absence of major external shocks, the government was able to improve the macroeconomic situation. – – Präsident Faure Gnassingbé agierte das ganze Jahr über aus einer Position der Stärke angesichts der gespaltenen und geschwächten Opposition. Überfällige politische und institutionelle Reformen sowie lokale Wahlen wurden auf unbestimmte Zeit verschoben. Die Menschenrechtslage verbesserte sich leicht, das Regime war jedoch weiterhin als ,,autoritär“ zu bezeichnen. Angesichts des wachsenden dschihadistischen Risikos in der Subregion belohnte die internationale Gebergemeinschaft Togos scheinbare politische Stabilität als Sicherheitsanker in Westafrika mit einer deutlichen Erhöhung der Entwicklungshilfe. Mit vielversprechenden Wachstumsaussichten, niedriger Inflation und dem Ausbleiben größerer externer Schocks konnte die Regierung die makroökonomische Lage verbessern.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2016; domestic policy; foreign affairs; socio-economic development; period under review 2016